Improving The Methodology Of Developing Professional Interests Of Students Based On An Innovative Approach - To‘lqinova Xolida To‘lqunovna (Genius Journals, 2024)
The rapid advancement of technology and the dynamic nature of the global economy necessitate the development of professional interests in students through innovative methodologies. This article explores the imperative need for adopting an innovative approach to cultivate professional interests, outlining effective strategies, and providing practical examples. By integrating modern pedagogical techniques, technological advancements, and real-world applications, this study aims to present a comprehensive framework for educators to foster a conducive environment for professional interest development in students.
Keywords: Innovative Education; Professional Interests